Произведения Александра Марданя в контексте „новой драмы” - Sibirnaja, Maria (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article attempts to allocate and analyze the most essential characteristics of plays by A. Mardan's, a popular Russian-speaking Ukrainian playwright, and to inscribe his work in the context of the dynamics of the phenomenon of the new drama. The attempt of the author is to understand a complex post-Soviet reality in order to reflect it in the artistic space of the drama. The plays demonstrate the destruction of habitual human values, including moral, ethical, aesthetic, and other norms that guide people in life. At the same time, his plays exploit the techniques and elements of various genres of mass culture. One may say that certain principles have become an integral quality of Mardan's plays such as the approach of the plays to the truth of life, the external everydayness, the use of elements of documentary theater and the theater of absurd, the construction of the plot with an eye for entertainment or scandalous intrigue, philosophical overtones and the author's attitude to the depicted world. This indicates that his plays may be regarded as works of ‘the new drama’ that occupy a worthy place in the contemporary Russian-language drama of the post-Soviet period.